Math, asked by 13bro, 1 year ago

Ltx>0 x-tanx/x-sinx​

Answers

Answered by Anonymous
92

Question :

Evaluate:

 \sf \lim _{x \to0} \:  \dfrac{x -  \tan \: x}{x -  \: sin \: x}

Solution :

 \sf \lim _{x \to0} \:  \dfrac{x -  \tan \: x}{x -  \: sin \: x}

Since 0/0 is of indeterminate form.

Then ,apply L'Hospital's Rule.

 \implies \: \sf \lim _{x \to0} \:  \dfrac{x -  \tan \: x}{x -  \: sin \: x} = \sf \lim _{x \to0} \:  \dfrac{ \frac{d(x -  \tan \: x)}{dx} }{ \frac{d(x -  \sin \: x)}{dx} }

\sf =  \lim _{x \to0} \:  \dfrac{1 -  \sec {}^{2}x }{1 -  \cos \: x}

This is again is of the 0/0 form , Use L'Hospital's rule again.

\sf =  \lim _{x \to0} \:  \dfrac{  - 2\sec {}^{2}x  \tan \: x }{ \sin \: x}

\sf =  \lim _{x \to0}   \dfrac{ - 2}{ \cos {}^{2} x}  \times  \dfrac{ \frac{  \cancel{ \sin \: x}}{ \cos \: x} }{ \cancel{\sin \: x}}

\sf =  \lim _{x \to0} \:  \dfrac{ - 2}{\cos  {}^{3} \: x}

\sf =  \lim _{x \to0}  - 2 \sec {}^{3} x

 =  - 2 \sec {}^{3} (0)

 =  - 2

Therefore ,

 \bf \lim _{x \to0} \:  \dfrac{x -  \tan \: x}{x -  \: sin \: x}  =  - 2

_____________________

About L'HOSPITAL'S Rule :

If f(a)=g(a)= 0 , then

 \sf \lim _{x \to \: a} \:  \frac{f(x)}{g(x)}  =  \sf \lim _{x \to \: a} \frac{f'(x)}{g'(x)}

Answered by Anonymous
34

Answer :-

\sf{\implies -2} \\

To solve :-

 \displaystyle \lim_{x \to 0}  \:  \:  \:  \:  \:  \:  \:  \:  \frac{x -  \tan(x) }{x -  \sin(x) }  \\

Applying L - hospital rule.

 \implies \displaystyle \lim_{x \to a } \:\:\:\: \frac{f(x)}{g(x)} = \displaystyle \lim_{x \to a } \:\:\:\: \frac{f'(x)}{g'(x)} \\

 \implies \displaystyle \lim_{x \to 0 } \:\:\:\: \frac{\frac{d}{dx} (x - \tan x ) }{\frac{d}{dx}( x - \sin x)} \\

 \implies \frac{d}{dx} (x)  -  \frac{d}{dx} ( \tan x ) = 1{x}^{0} - {\sec}^{2} x \\

\implies \frac{d}{dx} (x)  -  \frac{d}{dx} ( \sin x ) = 1{x}^{0} - \cos x \\

 \implies \displaystyle \lim_{x \to 0} \:  \:  \:  \:  \frac{1 -  { \sec(x) }^{2} }{1 -  \cos(x) }  \\

Again applying L - hospital rule

\implies \frac{d}{dx} (1)  -  \frac{d}{dx} ( {\sec}^{2} x ) = 0 - 2{\sec}^{2} x \tan x  \\

\implies \frac{d}{dx} (1)  -  \frac{d}{dx} ( \cos x ) = 0 - \sin x \\

\implies \displaystyle \lim_{x \to a } \:\:\:\: \frac{-2{\sec}^{2} x \tan x }{\sin x} \\

\implies \displaystyle \lim_{x \to a } \:\:\:\: \frac{-2 {\sec}^{2} x ( \tan x)}{\sin x} \\

\implies \displaystyle \lim_{x \to a }  \:  \:  \:  \frac{ - 2 { \sec(x)^{2}   \frac{ \sin(x) }{ \cos(x) }} }{ \sin(x) }  \\

\implies \displaystyle \lim_{x \to a } \:\:\:\:- 2 {\sec}^{2} x  \frac{1}{\cos x} \\

\implies \displaystyle \lim_{x \to a } \:\:\:\: -2 {\sec}^{3} x \\

\implies -2 \displaystyle \lim_{x \to a } {\sec}^{3} x \\

\large{\sf{\implies -2}} \\

Similar questions